Preparation, optimisation, and in vitro evaluation of [¹⁸F] AlF-NOTA-Pamidronic acid for bone imaging PET - Hishar Hassan; Muhamad Faiz Othman; Hairil Rashmizal Abdul Razak; Zainul Amiruddin Zakaria; Fathinul Fikri Ahmad Saad; Mohd Azuraidi Osman; Loh, Hui Yi; Zarif Ashhar; Jaleezah Idris; Mohd Hamdi Noor Abdul Hamid; Zaitulhusna M. Safee (Molecular Diversity Preservation International, 2022)
[¹⁸F] sodium fluoride ([¹⁸F] NaF) is recognised to be superior to [⁹⁹mTc]-methyl diphosphate ([⁹⁹mTc]Tc-MDP) and 2-deoxy-2-[¹⁸F]fluoro-D-glucose ([¹⁸F]FDG) in bone imaging. However, there is concern that [¹⁸F] NaF uptake is not cancer-specific, leading to a higher number of false-positive interpretations. Therefore, in this work, [¹⁸F] AlF-NOTA-pamidronic acid was prepared, optimised, and tested for its in vitro uptake. NOTA-pamidronic acid was prepared by an N-Hydroxysuccinimide (NHS) ester strategy and validated by liquid chromatography-mass spectrometry analysis (LCMS/MS). Radiolabeling of [¹⁸F] AlF-NOTA-pamidronic acid was optimised, and it was ensured that all quality control analysis requirements for the radiopharmaceuticals were met prior to the in vitro cell uptake studies. NOTA-pamidronic acid was successfully prepared and radiolabeled with ¹⁸F. The radiolabel was prepared in a 1:1 molar ratio of aluminium chloride (AlCl3) to NOTA-pamidronic acid and heated at 100 ◦C for 15 min in the presence of 50% ethanol (v/v), which proved to be optimal. The preliminary in vitro results of the binding of the hydroxyapatite showed that [¹⁸F] AlF-NOTApamidronic acid was as sensitive as [¹⁸F] sodium fluoride ([¹⁸F] NaF). Normal human osteoblast cell lines (hFOB 1.19) and human osteosarcoma cell lines (Saos-2) were used for the in vitro cellular uptake studies. It was found that [¹⁸F] NaF was higher in both cell lines, but [¹⁸F] AlF-NOTA-pamidronic acid showed promising cellular uptake in Saos-2. The preliminary results suggest that further preclinical studies of [¹⁸F] AlF-NOTA-pamidronic acid are needed before it is transferred to clinical research.